Efektivitas Pengelolaan Kelas Guru PAI di SMP Negeri 24 Medan - Neliwati, Neliwati; Situmorang, Hera Yanti; Nisa, Tia Khairun; Tiara, Irma (MODELING: Jurnal Program Studi PGMI, 2023)
In the teaching and learning process there are several factors that influence the success of the learning and teaching process, one of which is classroom management. Classroom management is an effort made by an educator with the aim of streamlining the teaching and learning process so that learning objectives can be achieved. This study aims to find out how a teacher at SMP Negeri 24 Medan can make classroom management effective in the teaching and learning process. From this research it is expected to find out how an educator can make classroom management effective as well as the supporting factors, inhibiting factors and efforts made by an educator. Based on the research conducted, it can be concluded that class management is carried out by PAI teachers at SMP Negeri 24 Medan, namely by changing the seating routes of students, teachers at SMP Negeri 24 Medan moving students who are not quick to grasp the lessons conveyed by the teacher to the front and students who are classified as smart are moved to sit in the back. This is done in order to make students who are less easy to grasp the learning conveyed by the teacher to be more focused in listening to what is conveyed by the teacher. In addition, the teacher also divides students into several groups according to the talents and interests of students. Class management carried out by PAI teachers at SMP Negeri 24 Medan is effectively carried out in the teaching and learning process because learning can be conveyed easily so that the objectives of learning can be achieved properly at SMP Negeri 24 Medan.